1997
DOI: 10.1074/jbc.272.52.32951
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Localization of P2 Receptors in Rat Submandibular Gland Acinar and Duct Cells

Abstract: [Ca 2؉] i and the Cl ؊ current were measured in isolated submandibular gland acinar and duct cells to characterize and localize the purinergic receptors expressed in these cells. In both cell types 2-3-benzoylbenzoyl (Bz)-ATP and ATP increased [Ca 2؉ ] i mainly by activation of Ca 2؉ influx. UTP had only minimal effect on [Ca 2؉ ] i at concentrations between 0.1 and 1 mM. However, a whole cell current recording showed that all nucleotides effectively activated Cl ؊ currents. Inhibition of signal transdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
89
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(95 citation statements)
references
References 29 publications
6
89
0
Order By: Relevance
“…Ablation of the P2X 7 gene had no effect on the salivary flow rate evoked by muscarinic receptor activation, but markedly reduced ATP-mediated fluid secretion and rescued the inhibitory effects of ATP on muscarinic receptor activation. Submandibular gland acinar cells from P2X 7 animals had dramatically impaired ATP-activated Ca 2ϩ signaling, consistent with this being the mechanism responsible for the reduction in ATP-mediated fluid secretion in these mice. Together, these results demonstrated that ATP regulates salivation, acting mainly through the P2X 7 receptor.…”
mentioning
confidence: 64%
See 3 more Smart Citations
“…Ablation of the P2X 7 gene had no effect on the salivary flow rate evoked by muscarinic receptor activation, but markedly reduced ATP-mediated fluid secretion and rescued the inhibitory effects of ATP on muscarinic receptor activation. Submandibular gland acinar cells from P2X 7 animals had dramatically impaired ATP-activated Ca 2ϩ signaling, consistent with this being the mechanism responsible for the reduction in ATP-mediated fluid secretion in these mice. Together, these results demonstrated that ATP regulates salivation, acting mainly through the P2X 7 receptor.…”
mentioning
confidence: 64%
“…An equal number of gender-and agematched (2-6-month-old) animals were utilized. Black Swiss/ 129 SvJ hybrid (Rochester colony) and C57BL/6 strain mice were obtained from Jackson Laboratories (Bar Harbor, ME), while P2X 7 Ϫ/Ϫ C57BL/6 mice were obtained from Pfizer (Benton, CT) and used as indicated. All experimental protocols were approved by the University of Rochester Animal Resources Committee.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In submandibular gland (SMG), metabotropic (P2Y 1 , P2Y 2 ) and ionotropic (P2X4, P2X7) receptor subtypes were found, both in basolateral and luminal membranes in acinar and ductal cells [6][7][8]. It was demonstrated that P2X7 activation regulates ionic currents and saliva volume and also induces reactive oxygen species production and inflammatory responses [9][10][11].…”
Section: Introductionmentioning
confidence: 99%